Evaluation of different CT maps for attenuation correction and segmentation in static 99mTc‐MAA SPECT/CT for 90Y radioembolization treatment planning: A simulation study. Issue 7 (9th June 2021) - Lu, Zhonglin; Chen, Gefei; Lin, Kuan‐Heng; Wu, Tung‐Hsin; Mok, Greta S. P.
Abstract : Purpose: Conventional 99m Tc‐macroaggregated albumin ( 99m Tc‐MAA) planar scintigraphy overestimates lung shunt fraction (LSF) compared to SPECT/CT. However, the respiratory motion artifact due to the temporal mismatch between static SPECT and helical CT (HCT) may compromise the SPECT quantitation accuracy by incorrect attenuation correction (AC) and volume‐of‐interest (VOI) segmentation. This study aims to evaluate AC and VOI segmentation effects systematically and to propose a CT map for LSF and tumor‐to‐normal liver ratio (TNR) estimation in static 99m Tc‐MAA SPECT/CT. Methods: The 4D XCAT phantom was used to simulate a phantom population of 120 phantoms, modeling 10 different anatomical variations, nine TNRs (2–13.2), nine tumor sizes (2–6.7 cm diameter), eight tumor locations, three axial motion amplitudes of 1, 1.5, and 2 (cm), and four LSFs of 5%, 10%, 15%, and 20%. An analytical projector for low‐energy high‐resolution parallel‐hole collimator was used to simulate 60 noisy projections over 360°, modeling attenuation and geometric collimator–detector response (GCDR). AC and VOI mismatch effects were investigated independently and together, using cine average CT (CACT), HCT at end‐inspiration (HCT‐IN), mid‐respiration (HCT‐MID), and end‐expiration (HCT‐EX) respectively as attenuation and segmentation maps. SPECT images without motion, AC, and VOI errors were also generated as reference. LSF and TNR errors were measured as compared to the ground truth. Results: HCT‐MID has slightly better performance for AC effect compared with other CT maps in LSF and TNR estimation, while HCT‐EX and HCT‐MID perform better for VOI effect. For a respiratory motion amplitude of 1.5 cm and a LSF of 5%, the LSF errors are 19.56 ± 4.58%, −6.79 ± 1.74%, 77.29 ± 14.74%, and 111.25 ± 18.29% corresponding to HCT‐MID, HCT‐EX, HCT‐IN, and CACT in static SPECT. The TNR errors are −12.38 ± 6.42%, −20.55 ± 11.25%, −20.89 ± 9.98%, and −22.89 ± 14.38% respectively. HCT‐MID has the best performance for LSF estimation for LSF > 10% and TNR estimation, followed by HCT‐EX, HCT‐IN, and CACT. Conclusions: The HCT‐MID is recommended for AC and segmentation to alleviate respiratory artifacts and improve quantitation accuracy in 90 Y radioembolization treatment planning. HCT‐EX would also be a recommended choice if HCT‐MID is not available.